TINDAK PIDANA KORUPSI MENERIMA UANG YANG DILAKUKAN OLEH PEGAWAI NEGERI SIPIL - Dian Natasha; Setiyono (Fakultas Hukum Universitas Trisakti, 2022)
A civil officer and the landowner both took use of the regional innovation program offered by the Ministry of Research, Technology, and Higher Education in 2016 to engage in criminal corruption. How appropriately civil servants' receipt of money is governed by the provisions of Article 5 (2) of Law Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 Concerning the Eradication of Corruption Crimes (PTPK) and the Assembly's legal considerations is the formulation of the problem. The judge with regard to the criminal penalties meted out to corruption offenders. This article is normative legal, descriptive, secondary data kinds, data collecting for literature studies, qualitative data analysis, and using deductive reasoning. The findings of the study, the discussion, and the conclusion, indicate that the defendant should be charged with the felony of corrupt act, as defined in Article 12 letter an of the PTPK Law, because the defendant's actions are suspected, namely that he accepted promises and gifts without declining the offer even though he knew the gift was intended to persuade him to act in a manner that involved his position as the head of the housing agency.